ENVIRONMENTAL CONTROL OF NANNOPLANKTON AND FORAMINIFERA ASSEMBLAGES IN MADURA WATERS - Vijaya Isnaniawardhani (BULLETIN OF THE MARINE GEOLOGY, 2009)
Nannoplankton is widely used for determining age of sediments following the other microorganism foraminifera since the late 1960s; and it was started being used for marine geography study in the year of 1984. This topic interests to be done in Indonesia as one of the tropic region. The research covered a study about environment using nannoplankton and it is compared with the same study using foraminifera. Methods of the study include: (1) collecting secondary data and samples; (2) collecting field data record; (3) laboratory analyses upon sediment samples to determine the content of nannoplankton and foraminifera (micropaleontology analyses), the texture and composition of minerals (by means of grain size, petrology megascopic and microscopic analyses) (4) intergrating all of the analyses result. Madura waters can be divided into four zones, among all : (I) inner shelf (water depth less than 30 m) in Madura Strait, (II) inner shelf in open marine north of Madura, (III) outer shelf (water depth 30 to 80 m) in Madura Strait, and (IV) outer shelf in open marine north of Madura. Inner shelf in the Madura Strait (Zone I) is characterized by less than 1% sediment of nannoplankton (are made up of Gephyrocapsa oceanica); rare assemblages of benthic foraminifera only (Ammonia spp., arenaceous carbonate test taxa such as : Ammobaculites spp., Textularia agglutinans, Haplophragmoides spp., and milliolidae). Inner shelf open marine north of Madura (Zone II) yielded few nannoplankton assemblages, dominated by Gephyrocapsa oceanica with low number of Emiliania huxleyi, Helicosphaera carteri, H. pavimentum, H. walichii and Pontosphaera spp; common foraminifera assemblages consist of rare planktic Globigerinoides ruber, G. trilobus sacculiferus, G. conglobatus with one or two dominant benthic (Elphidium spp, Ammonia spp., Pseudorotalia spp., Asterorotalia spp.). Outer shelf of Madura Strait (Zone III) assigned by common nannoplankton assemblages, dominated by Gephyrocapsa oceanica and Emiliania huxleyi with few to common Helicosphaera carteri, H. pavimentum, H. wallichii, Pontosphaera spp., Calcidiscus leptoporus, Umbellosphaera irregularis and Umbilicosphaera spp.; common benthic foraminifera assemblages Elphidium spp, Ammonia spp., Cibicides spp., Pseudorotalia spp., and Asterorotalia spp. with rare planktic Globigerinoides ruber, G. trilobus sacculiferus, and G. conglobatus. In the outer shelf open marine north of Madura (Zone IV), it is recorded abundant of nannoplankton Gephyrocapsa oceanica, Emiliania huxleyi, Helicosphaera carteri, H. pavimentum, H. wallichii, Pontosphaera spp., Discoaster spp., Calcidiscus leptoporus, Umbellosphaera irregularis, Umbilicosphaera spp.; the presence of moderate divers and abundance of planktic foraminifera Globigerina calida, Pulleniatina obliquiloculata, Orbulina universa, Hastigerina aequilateralis with common abundance benthic Bolivina spp., Bulimina spp., Cibicides spp., Pseudorotalia spp., Asterorotalia spp., Lenticulina spp., Cassidulina spp., Siphonina spp., the presence of Uvigerina spp. are noted. The most significant physical environment parameter of each zone controlling appearance of marker species and abundancy of microorganism assemblages are bathymetry, salinity, temperature, pH and sediment due to fluvial supply. Keywords : nannoplankton, foraminifera, environment, marker species, Madura Waters Nannoplankton telah digunakan secara luas untuk penentuan umur sedimen di samping mikroorganisme lain, foraminifera, sejak tahun 1960-an; dan mulai digunakan untuk studi geografi laut pada tahun 1984. Kajian ini menarik untuk dilakukan di Indonesia yang termasuk daerah tropis. Studi ini mempelajari perubahan lingkungan berdasarkan analisis nannoplankton, dibandingkan dengan foraminifera yang umum dipakai untuk kegunaan sejenis. Metode penelitian mencakup : (1) pengumpulan data sekunder dan sampel; (2) pengambilan data lapangan; (3) pekerjaan laboratorium meliputi analisis mikropaleontologi dan petrologi ; serta (4) integrasi seluruh hasil analisis. Perairan Madura dapat dibedakan menjadi empat zona, yaitu: (I) Paparan dalam (kedalaman muka air laut kurang dari 30 m) di Selat Madura; (II) Paparan dalam pada laut terbuka di Perairan Utara Madura; (III) Paparan luar (kedalaman muka air laut 30 hingga 80 m) di Selat Madura; dan (IV) Paparan luar pada laut terbuka di Perairan Utara Madura. Paparan dalam di Selat Madura (Zona I) dicirikan oleh kumpulan nannoplankton kurang dari 1% total sedimen (Gephyrocapsa oceanica); foraminifera bentik jarang (Ammonia spp., cangkang gamping pasiran seperti Ammobaculites spp., Textularia agglutinans, Haplophragmoides spp., dan miliolida). Paparan dalam di laut terbuka (Zona II) dicirikan oleh nannoplankton kurang melimpah yang didominasi oleh Gephyrocapsa oceanica dengan beberapa Emiliania huxleyi, Helicosphaera carteri, H. pavimentum, H. walichii, Pontosphaera spp; foraminifera cukup melimpah dengan plankton Globigerinoides ruber, G. trilobus sacculiferus, G. conglobatus dalam jumlah jarang serta satu atau dua jenis bentik yang dominan (Elphidium spp, Ammonia spp., Pseudorotalia spp., Asterorotalia spp.). Paparan luar di Selat Madura (Zona III) dicirikan oleh nannoplankton dalam jumlah yang umum, didominasi oleh Gephyrocapsa oceanica dan Emiliania huxleyi dengan beberapa Helicosphaera carteri, H. pavimentum, H. wallichii, Pontosphaera spp., Calcidiscus leptoporus, Umbellosphaera irregularis, Umbilicosphaera spp.; foraminifera bentik jumlahnya umum seperti Elphidium spp, Ammonia spp., Cibicides spp., Pseudorotalia spp., dan Asterorotalia spp. dengan foraminifera planktik seperti Globigerinoides ruber, G. trilobus sacculiferus, dan G. conglobatus dalam jumlah jarang. Di paparan luar laut terbuka (Zona IV) teridentifikasi nannoplankton yang melimpah seperti Gephyrocapsa oceanica, Emiliania huxleyi, Helicosphaera carteri, H. pavimentum, H. wallichii, Pontosphaera spp., Discoaster spp., Calcidiscus leptoporus, Umbellosphaera irregularis, Umbilicosphaera spp.; dan beragam jenis foraminifera planktik seperti Globigerina calida, Pulleniatina obliquiloculata, Orbulina universa dan Hastigerina aequilateralis serta foraminifera bentik seperti Bolivina spp., Bulimina spp., Cibicides spp., Pseudorotalia spp., Asterorotalia spp., Lenticulina spp., Cassidulina spp., Siphonina spp. dan Uvigerina spp. dalam jumlah yang umum. Parameter lingkungan fisik yang paling berpengaruh dalam mengontrol kehadiran spesies penunjuk (indikator) dan kelimpahan kumpulan mikroorganisma adalah: batimetri, salinitas, temperatur, pH dan sedimen. Katakunci : nannoplankton, foraminifera, lingkungan, spesies penunjuk, Perairan Madura